The complete chloroplast genome sequence of Vitis vinifera × Vitis labrusca ‘Shenhua’ - Lipeng Zhang; Dinghan Guo; Miaomiao Liu; Feifei Dou; Yi Ren; Dongmei Li; Shiping Wang; Lei Wang; Chao Ma; Qian Zha; Ling Su; Lei Gong; et al. (Mitochondrial DNA. Part B. Resources, 2021)
Vitis vinifera × Vitis labrusca ‘Shenhua’ is a tetraploid grape, a Franco-american species. This study first published the complete chloroplast genome of Vitis vinifera × Vitis labrusca ‘Shenhua’ was assembled. The chloroplast genome is 160928 bp in length, including a large single copy region (89,148 bp), a small single-copy region (19,072 bp) and a pair of inverted repeats of 26,354 bp. The chloroplast genome encodes 133 genes, comprising 88 CDSs, 37 tRNA genes and 8 rRNA genes. The phylogenetic tree demonstrated that Vitis vinifera × Vitis labrusca ‘Shenhua’ is different from the other 16 varieties.